2000
DOI: 10.1088/0953-8984/12/14/305
|View full text |Cite
|
Sign up to set email alerts
|

An x-ray diffraction and Raman spectroscopy investigation of A-site substituted perovskite compounds: the (Na1-xKx)0.5Bi0.5TiO3(0lexle1) solid solution

Abstract: The (Na1 - x Kx )0.5 Bi0.5 TiO3 perovskite solid solution is investigated using x-ray diffraction (XRD) and Raman spectroscopy in order to follow the structural evolution between the end members Na0.5 Bi0.5 TiO3 (rhombohedral at 300 K) and K0.5 Bi0.5 TiO3 (tetragonal at 300 K). The Raman spectra are analysed with special regard to the hard modes and suggest the existence of nano-sized Bi3+ TiO3 and (Na1 - 2x K2x )+ TiO3 clusters. The complementary use of XRD and Raman spectroscopy suggests, in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
237
4
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(291 citation statements)
references
References 42 publications
36
237
4
3
Order By: Relevance
“…7(a). The spectrum is consistent with previous reports, 15,[21][22][23][24] where it was assigned as belonging to the pseudo-rhombohedral R3c phase, for which a total of 13 Ramanactive modes (Γ Raman, R3c =4A 1 +9E) are expected. 23 Three main regions can be discerned.…”
Section: Raman Spectroscopy Of Unmodified and Fe-modified Nbtsupporting
confidence: 91%
See 1 more Smart Citation
“…7(a). The spectrum is consistent with previous reports, 15,[21][22][23][24] where it was assigned as belonging to the pseudo-rhombohedral R3c phase, for which a total of 13 Ramanactive modes (Γ Raman, R3c =4A 1 +9E) are expected. 23 Three main regions can be discerned.…”
Section: Raman Spectroscopy Of Unmodified and Fe-modified Nbtsupporting
confidence: 91%
“…[16][17][18][19] Raman spectroscopy has been used to study phase transitions and the nanoscale structural characteristics of NBT and its solid solutions. 15,[20][21][22][23][24] Due to challenges of intrinsic broadening and overlapping of phonon modes in the assignment of mode symmetries, structural analysis thus relies on analyzing soft-mode or hard-mode behavior as a function of composition, pressure or temperature. 15,[21][22][23][24] Other studies in NBT-BT 25 and NBT-SrTiO 3 24 generally confirmed that transitions involving the ferroelectric behavior are related to subtle local structural distortions and phase coexistence.…”
Section: As Well Asmentioning
confidence: 99%
“…Bismuth sodium titanate (Bi 0.5 Na 0.5 )TiO 3 (BNT) has been recognized as one of the most promising candidates for the lead-free piezoelectric material [5,[10][11][12][13]. To clarify the origin of its ferroelectricity, the crystal structure has been intensively analyzed in detail [14][15][16][17][18][19][20][21][22]. The averaged structure of BNT has been reported to be a rhombohedral structure in space group R3c.…”
Section: Open Accessmentioning
confidence: 99%
“…For example, neutron scattering and high-resolution synchrotron x-ray diffraction (XRD) identified a relatively wide transition range over which T and R phases coexist, [16][17][18] and transmission electron microscopy (TEM) images of powder samples evidenced an intermediate modulated orthorhombic (O) phase between the R and T phases in the temperature range between 230 and 300 C. 19,20 Raman spectroscopy represents another local probe to study NBT-x%BT. 21,22 Theoretically, for the ferroelectric rhombohedral R3c phase of NBT-x%BT, there are 13 Raman active modes, 23 including 7A 1 and 6E modes. Prior experimental investigations have shown that these peaks are broad and cannot all be resolved from each other but can be categorized into those pertaining to one of three frequency ranges.…”
Section: Introductionmentioning
confidence: 99%